Effect of blend composition and organoclay loading on the nanocomposite structure and properties of miscible poly(methyl methacrylate)/poly(styrene-co-acrylonitrile) blends - Tiwari, Rajkiran R.; Natarajan, Upendra (Polymer Engineering and Science, 2011)
Organically-modified montmorillonite clay nanocomposites of poly(styrene-co-acrylonitrile) (SAN), poly(methyl methacrylate) (PMMA) and SAN/PMMA miscible blend are investigated. Structure characteristics at the nanoscale and microscale and thermal and tensile properties are studied as a function of polymer blend composition and filler loading fraction. Blend miscibility and T(g) are unaffected by up to 10% by wt. organoclay. Thermal degradation stability increases with SAN content and exhibits an optimum value of clay loading. Stiffness shows significant improvement. Tensile strength and elongation-at-break suffer as a result of nanocomposite formation. Modulus shows a maximum enhancement of 57% (5 +/- 0.06 GPa at 10 wt% filler, 20/80 SAN/PMMA) and varies linearly with clay fraction for all compositions of matrix phase. Predictions of Halpin-Tsai composite model are in excellent agreement with the experimental behavior over full range of polymer blend composition. Fundamental aspects of a polymer blend-clay nanocomposite are clarified, such as lack of additional synergy between clay platelets and matrix, and tensile ductility reduction, compared with polymer-clay system. POLYM. ENG. SCI., 51:979-991, 2011. (C) 2011 Society of Plastics Engineers